The Accuracy of FIBROTEST for cotton fiber length and strength measurements: study sensitivity of cotton fiber instrument (CCS) - Shalaby, Mona (European Journal of Applied Sciences, 2022)
For investigation of the accuracy of FIBROTEST used two categories of standard calibration cotton, long/strong and short/weak. The present study was carried out at Cotton Research Institute (CRI), Agricultural Research Center (ARC), Giza, Egypt.Before carrying out the tests, the cotton samples were incubated in the BINDER equipment for two days to reach the standard conditions for the tests. The measurements that were analyzed are: length measurements properties, i.e.,upper half mean, upper half mean relative to HVI, 50% span length, 2.5% span length, mean length,uniformity index, uniformity index relative to HVI, short fiber content and short fiber index, and strength properties,i.e., absolute strength, strength relative to HVI, elongation, bundleweight, linear density, force, work and time atbreak. Results indicated that fiber length and strength measurements showed few differences for long / strong and short / weak cotton.The values of these measurements were distributed symmetrically with low skewness and kurtosis.The FIBROTEST gave values for UHM, UI and strength very close to their actual values.It can be admitted that this device is accurate in measuring, but to ensure this is achieved, especially for fiber strength, it is necessary to test a large number of subsamples.Since linear density is the actual effect of fiber strength, so to avoid this, emphasis is placed on linear density to achieve a more accurate measure of strength. The most suitable linear density for the long / strong cotton was 1723 and for the short / weak was 1274.To obtain a specific and repeated amount of linear density to achieve an accurate measurement of strength, the Fibro-sampler has to be considered in any development or modernization of the FIBROTEST device.